Pengaruh Pemberian Ekstrak Biji Kopi Robusta (Coffea canephora) Lampung Terhadap Gambaran Histopatologi Tubulus Proksimal Ginjal Tikus Putih (Rattus norvegicus) Jantan Galur Sprague-dawley yang Diinduksi Monosodium Glutamat - Salsabila, Aina; Wulan, Anggraeni Janar; Rodiani, Rodiani (Medula, 2024)
Excessive consumption of monosodium glutamate can form free radicals and is nephrotoxic which causes damage to organs, one of which is the kidneys, especially in the proximal tubule. Chlorogenic acid compounds contained in coffee beans have potential as antioxidants and nephroprotective agents. Coffee consumption at a certain dose is assumed to prevent and or reduce damage to the proximal kidney tubules of rats caused by free radicals. This research is an experimental study with a completely randomized design (CRD) with a Posttest Only Control Group Design approach. This research was conducted for 14 days. The samples used were 25 rats which were divided into 5 groups, namely K- (aquades 3 ml/day), K+ (MSG 4 g/kgBW/day), P1, P2, and P3 (MSG 4 g/kgBW/day). and Lampung robusta coffee bean extract 1 ml/200gBW/day with a concentration of 0.006 g/ml; 0.012 g/ml; 0.024 g/ml respectively) with each group consisting of 5 rats. Kidney histopathological assessment was carried out by observing kidney preparations in 5 visual fields each in 400x magnification. The mean total score of proximal tubular damage in groups K-, K+, P1, P2, and P3 respectively was 2.48; 3.40; 2.80; 2.64; 3.04. One Way ANOVA test obtained p value = 0.001 (p <0.05). Post Hoc LSD test on proximal tubular damage scores showed a significant difference (p<0.05) between K- and K+ (p=0.000), K- and P3 (p=0.008), K+ and P1 (p=0.005) , K+ with P2 (p=0.001), and P2 with P3 (p=0.047). There is an effect of administration of Lampung Robusta (Coffea canephora) coffee bean extract on the histopathological appearance of the kidney proximal tubules of male rats (Rattus norvegicus) strain Sprague-Dawley induced by monosodium glutamate.